A facile hydrothermal recovery of nano sealed MnO2 particle from waste batteries: An advanced material for electrochemical and environmental applications. (September 2016) - Mylarappa, M; Lakshmi, V Venkata; Mahesh, K R Vishnu; Nagaswarupa, H P; Raghavendra, N
Abstract: This work deliberates a method for manganese (Mn) recovery as manganese oxide obtained by leaching of waste batteries with 3M sulphuric acid. The Experimental test for the recovery of Mn present within the waste dry cell batteries were carried out by a reductive leachant. Elemental composition of leached sample was confirmed by Energy Dispersive X-ray analysis (EDAX), and Surface morphology of the recovered MnO2 was examined by using Scanning Electron microscopy (SEM). Phase composition was confirmed from X-ray Diffractro meter (XRD). The obtained leached solution was treated with 4M NaOH, yielded to Manganese Dioxide with high extraction degree, while it do not touches the Zn content within the solutions. The recovered samples were characterized using XRD, EDAX, SEM and Fourier transform infrared spectrometry (FTIR). The electrochemical properties of the as-recovered sample from leached solution was examined used cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Remarkably, the 80 wt.% MnO2 displays reversibility, diffusion constant, smaller equivalent series resistance and charge transfer resistance in 0.5M NaOH showed superior results as compared to alternative electrolytes. The ideal capacitive behaviour of MnO2 electrode and nano particle was applied to photocatalytic degradation of dyes.